Hypertension in people in middle and late adulthood during sports and physical training - M. O. Vyalova; I. M. Sokolov; A. S. Shmoylova; Yu. G. Schwartz (Кардиоваскулярная терапия и профилактика, 2020)
Aim. Comparative analysis of changes in blood pressure (BP) measured before and after the physical exertion in veteran athletes and persons practicing physical training (late and middle adulthood).Material and methods. The 200 competitive athletes and 45 persons practicing physical training, aged 40 to 72 years were questioned in order to identify the main factors of cardiovascular risk. All measurements and results obtained under this research were treated with regard to the diagnosis of hypertension (HTN), prior determined by a physician, and also to the administered therapy.Results. A total of 54,7% of subjects was diagnosed with the HTN, with 32,6% out of them not taking antihypertensives. 53% of athletes and 62.2% persons practicing physical training were diagnosed with the arterial hypertension. Among athletes, the HTN incidence was 53%, among persons practicing physical training — 62,2%. Among athletes, 49% had pre-exercise elevated systolic BP (SBP) and 42,5% had elevated pre-exercise diastolic BP (DBP). While only 17% of persons practicing physical training demonstrated the elevated SBP and only 13,3% of them were recorded with the elevated DBP. One third of athletes without HTN in their everyday activities were diagnosed with the elevated both SBP and DBP during physical exertion. Immediately after the exercise stress, 39% of all the examined athletes were diagnosed with the elevated post-exercise SBP, and 36,2% of them with the elevated post-exercise DBP. Among persons practicing physical training, 33% of subjects were diagnosed with the elevated postexercise SBP, and 24,4% of them with the elevated post-exercise DBP.Conclusion. A major part of the athletes are diagnosed with the elevation in pre- and post-exercise BP. Whereas, persons practicing physical training demonstrate normal average pre- and post-exercise SBP and DBP values in most of the cases. Post-exercise differences in BP values in athletes and persons practicing physical training are almost leveled out. Post-exercise HTN >140/90 mm Hg is detected both in people with HTN receiving antihypertensive therapy, and in people without HTN. Elderly people involved in sports or fitness have significant differences in the response of BP to the exertion. However, in a significant part of this HTN people, BP changes during exercise are in the hypertensive range and can be an additional cardiovascular risk factor.